Cellular and molecular studies of the effects of a selective COX-2 inhibitor celecoxib in the cardiac cell line H9c2 and their correlation with death mechanisms - Sakane, K. K.; Monteiro, C. J.; Silva, W.; Silva, A. R.; Santos, P. M.; Lima, K. F.; Moraes, K. C. M. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2014)
Cardiovascular disease is one of the leading causes of death worldwide, and evidence indicates a correlation between the inflammatory process and cardiac dysfunction. Selective inhibitors of cyclooxygenase-2 (COX-2) enzyme are not recommended for long-term use because of potentially severe side effects to the heart. Considering this and the frequent prescribing of commercial celecoxib, the present study analyzed cellular and molecular effects of 1 and 10 mu M celecoxib in a cell culture model. After a 24-h incubation, celecoxib reduced cell viability in a dose-dependent manner as also demonstrated in MTT assays. Furthermore, reverse transcription-polymerase chain reaction analysis showed that the drug modulated the expression level of genes related to death pathways, and Western blot analyses demonstrated a modulatory effect of the drug on COX-2 protein levels in cardiac cells. In addition, the results demonstrated a downregulation of prostaglandin E2 production by the cardiac cells incubated with celecoxib, in a dose-specific manner. These results are consistent with the decrease in cell viability and the presence of necrotic processes shown by Fourier transform infrared analysis, suggesting a direct correlation of prostanoids in cellular homeostasis and survival.
Keywords: Cellular and molecular analyses; Cell death; Cyclooxygenase-2 inhibitor; H9c2 cardiac cell line